English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2x +4y = 8
-5x +3y = 5

Can anyone help remind me how to do this. I DONT NOT JUST WANT AN ANSWER. I want to understand how to do it

2006-11-28 06:03:37 · 8 answers · asked by Perfect-Angel84 2 in Science & Mathematics Mathematics

slightly peeved - original equation definately right. They are level 3

2006-11-28 06:18:33 · update #1

8 answers

I'm going from memory

try multiply all terms in top eq by 5

giving 10x + 20y = 40

then the bottom by 2

giving -10x + 6y = 10

then add the two gives 26y = 50

work back 2x + 4(1.923) = 8
thus 2x + 7.69 = 8
2x = 8 - 7.69
2x = 0.31
x = 0.155

therefore y = 1.923 and x = 0.155

you have to find the lowest common multiple of two of the terms, whether it be x or y.

i hope this helps but it looks wrong to me. did u get the original eq right and what level are they at?

good luck

2006-11-28 06:15:54 · answer #1 · answered by Anonymous · 0 0

you yave to make either the x's or the y's the same value by multiplying the whole equation by a common denominator. If you make the x's in your equation the same by multiplying the top line by 5 and the bottom line by 2 it gives the following

10x + 20y = 40

-10x + 6y = 10

You can then add the equations together, the plus 10 in the top line cancells out the minus 10 in the bottom (10 + (-10) = 0). This leaves you with just a y value

26y = 50

y = 50/26

(This can then be cancelled down to y = 25/13 by dividing both numbers by 2 it means the same thing)

Once you have done this you can substitute the y value back into one of the equations to find the x value.

2x + 4(25/13) = 8

The answers obviously wont be whole numbers
Hope this helps

2006-11-28 14:18:08 · answer #2 · answered by Atlanta 3 · 0 0

First, you need to decide which variable (x or y) to eliminate. Then you need to have that variable have the same value in each equation, so that you may eliminate it. For the equations in your question, I would choose y as the variable to eliminate (it doesn't matter which you choose). Multiply the 1st equation by 3 (the coefficient of y in the 2nd equation) and multiply the second by 4 (the coefficient of y in the 1st equation) as follows:

3 X (2x + 4y) = 3 X 8 gives us 6x + 12Y = 24
4 X (-5x + 3y) = 4 X 5 gives us -20x +12y = 20

Now subtract one equation from the other as follows:

6x + 12y = 24
-(-20x + 12y) = -20
------------------------------
26x + 0y = 4

Next, divide both sides by the coefficient of x (26 in this case) to obtain the value of x. (26/4 or 6.5)

Finally, substitute the value of x in either of the equations and you will find the value of y.

2(6.5) + 4y = 8
13 + 4y = 8
4y = 8 -13
4y = -5
y = -5/4 = -1.25

2006-11-28 14:24:57 · answer #3 · answered by Weird Darryl 6 · 0 0

process of elimination
you have to multiply the top equation with 5 and the bottom with two, that way you can eliminate the x and find the y and then you plug what you have for y to find x
5(2x+4y=8)---> 10x+20y=40
2(-5x+3y=5)---->-10x+6y=10
the 10x and -10x cancel each other then you have
20y+6y=50-----> 26y=50 ===>y=25/13
then plug 25/13 for y to find x
2x+4(25/13)=8--> 2x=4/13--> 4/13 divided by 2=> x=2/13
to make sure you got the right answer just plug the answers in to make sure you get the same answer
hope this helps you, **** luck

2006-11-28 14:20:55 · answer #4 · answered by Anonymous · 0 0

One of many ways actually...

Here's another one:

2x + 4y = 8 <=> x + 2y = 4 (1)

-5x + 3y = 5 <=> -x + (3/5)y = 1 (2)

(1) + (2) <=> 2y + (3/5)y = 5 <=> y = 25/13

And then in (1) to find x.

2006-11-28 14:23:49 · answer #5 · answered by rabencor 1 · 0 0

You have to multiply the first and second equations so that you get a common term in both equations. For eg, I'll multiply the first equation by 10 and the second by 2 to get 10x in both equations so I can eliminate the term. So in this case, you get 10x + 20y=40 for the first equation and -10x+6y=10 for the second equation. Now just add them to cancel the 10x. So you get 26y=50. Now solve fot y by dividing 50 by 26. then replace in the first equation. ANS: y=1.923(3 d.p) and 2x + 4(1.923)=8.
Therefore x=0.1538(4 d.p)

2006-11-28 14:23:33 · answer #6 · answered by Y L 2 · 0 0

you want to get either x or y
with the same coefficient
3(2x+4y=8)
4(-5x+3y=5)
6x+12y=24.........(1)
-20x+12y=20......(2)

we now have the y's with the
same coefficient,namely 12
so,we subtract (2) from(1)
26x=4>>x=2/13
now substitute this value for x
into (1)
6*2/13+12y=24
12y=24-12/13
y=2-1/13=1 12/13

therefore,x=2/13 and
y=25/13 =1 12/13

i hope that this helps

2006-11-28 18:20:23 · answer #7 · answered by Anonymous · 0 0

5(2x+4y)=8
2(-5x+3y)=5

10x+20y=40
-10x+6y=10

26y=50
y=25/13

2x+4(25/13)=8
2x+100/13=8
2x=4/13
x=2/13

2006-11-28 14:09:20 · answer #8 · answered by      7 · 0 0

fedest.com, questions and answers